2021
DOI: 10.1371/journal.pone.0247453
|View full text |Cite
|
Sign up to set email alerts
|

Modeling driver behavior in the dilemma zone based on stochastic model predictive control

Abstract: Driver behavior is considered one of the most important factors in the genesis of dilemma zones and the safety of driver-vehicle-environment systems. An accurate driver behavior model can improve the traffic signal control efficiency and decrease traffic accidents in signalized intersections. This paper uses a mathematical modeling method to study driver behavior in a dilemma zone based on stochastic model predictive control (SMPC), along with considering the dynamic characteristics of human cognition and exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Autonomous vehicles have been projected to introduce a wide range of impacts, such as reduced road accidents, vehicle emissions, cost of travel or increased productivity [2][3][4][5]15], driving under challenging weather conditions [16]. Furthermore, researchers have pointed out the potential AV impact on highway capacity, e.g., via platooning [17][18][19] driving behaviour [20,21], public transport services [22,23], the value of travel time [24,25], private parking infrastructure [26], accessibility and induced demand [27] among others. A lot of the literature has primarily focused on short-term implications of AVs [4,5], but research community attention has also been shifted towards longer-term socio-technical changes [5,9,15,28].…”
Section: Introductionmentioning
confidence: 99%
“…Autonomous vehicles have been projected to introduce a wide range of impacts, such as reduced road accidents, vehicle emissions, cost of travel or increased productivity [2][3][4][5]15], driving under challenging weather conditions [16]. Furthermore, researchers have pointed out the potential AV impact on highway capacity, e.g., via platooning [17][18][19] driving behaviour [20,21], public transport services [22,23], the value of travel time [24,25], private parking infrastructure [26], accessibility and induced demand [27] among others. A lot of the literature has primarily focused on short-term implications of AVs [4,5], but research community attention has also been shifted towards longer-term socio-technical changes [5,9,15,28].…”
Section: Introductionmentioning
confidence: 99%
“…Papers Percentage of studies Simulator [54], [46], [66], [89], [90], [76], [82], [81], [47], [34], [35], [69], [79], [104], [80], [57], [70], [92], [108], [93], [94], [51], [88], [50] 25% Camera [29], [38], [40], [53], [75], [84], [106], [107], [34], [77], [77], [77], [77], [86], [87], [103] 17% GPS [31], [33], [40], [43], [45], [58], [62], [67], [68], [83],…”
Section: Data Sourcementioning
confidence: 99%
“…The concept of cooperative game theory is introduced to describe the conflicts and cooperation between the uncertain driver behaviors and other subsystems, aiming to enhance the stability of electric vehicle operation in the event of motor faults. Li et al [72] modeled driver behavior in the signal dilemma zone using SMPC. The simulation experiments demonstrated that the proposed driver behavior model framework based on SMPC accurately captures vehicle motion and dynamics in the dilemma zone.…”
Section: Driving Process Uncertaintymentioning
confidence: 99%